Special Fresno City Council Swearing-In Session in Wine Room at Valdez Hall - Watkins, Howard::::::::: (1983)
Mayor Daniel Whitehurst presenting plaque and shaking hands with Leonel Alvarado; Joe Williams, Jackie Ryle